2009
DOI: 10.12938/bifidus.28.1
|View full text |Cite
|
Sign up to set email alerts
|

Copper Binding by Lactic Acid Bacteria (LAB)

Abstract: Western diet is frequently low in essential metal ions. A common method for preventing metal ion deficiency is pharmacological supplementation, especially in a highly available form such as metalo-protein complexes. Accordingly, in this work, specific lactic acid bacteria were assessed for their ability to bind copper ions. Significant amounts of copper ions were bound, and the binding potential was found to be strain specific. Differences among the strains were evaluated with the Langmuir model for biosorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Several Lactobacillus strains have been reported to resist various metals ion at different concentration levels. Most studies emphasize on bioremediation or decontamination of heavy metals in the body and environmental perspectives [19,25,[42][43][44][45][46][47][48]. However, less is known about their capacity to tolerate with Zn 2+ and produce zinc nanomaterials simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Lactobacillus strains have been reported to resist various metals ion at different concentration levels. Most studies emphasize on bioremediation or decontamination of heavy metals in the body and environmental perspectives [19,25,[42][43][44][45][46][47][48]. However, less is known about their capacity to tolerate with Zn 2+ and produce zinc nanomaterials simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, we have reported a zinc-tolerant probiotic with the highest MTC value of 500 mM compared to other reports in the literature. In fact, the variations in resistance against metal ions between bacterial species are due to different properties of the bacteria, which include cell wall structure, functional groups and surface area [20,26,46].…”
Section: O-h Stretching and N-h Asymmetric Stretchingmentioning
confidence: 99%
“…Previous reports have revealed that some lactobacilli, including Lactobacillus rhamnosus, L. plantarum, and L. brevis, can bind and remove heavy metals such as cadmium, lead, and copper in vitro (19,20). Besides the cadmium binding capacity, lactobacilli are also known to have antioxidative properties in human subjects, which may be another important characteristic for cadmium toxicity protection (21)(22)(23).…”
mentioning
confidence: 99%
“…As the pH of the solution increased, the binding capacity of the lactobacilli for Cu also increased ( Figure 2), probably due to a larger number of negatively charged carboxyl and phosphate groups on the cell surface [29]. Several authors have described a pH of 5.0 as optimal for the metal biosorption by lactobacilli [30,31]. Although at even higher pH values more negatively charged functional groups would be available, these conditions are remote and unsuitable, as they promote formation of insoluble copper(II) hydroxides and precipitates.…”
Section: Biosorptionmentioning
confidence: 99%